2019
DOI: 10.1186/s13058-018-1086-8
|View full text |Cite
|
Sign up to set email alerts
|

A method of producing genetically manipulated mouse mammary gland

Abstract: BackgroundTo obtain a deep understanding of the mechanism by which breast cancer develops, the genes involved in tumorigenesis should be analyzed in vivo. Mouse mammary gland can regenerate completely from a mammary stem cell (MaSC), which enables us to analyze the effect of gene expression and repression on tumorigenesis in mammary gland regenerated from genetically manipulated MaSCs. Although lentiviral and retroviral systems have usually been applied for gene transduction into MaSCs, they are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…Mouse mammary glands can regenerate completely by the use of mammary stem cells (MaSCs). To examine the mechanism by which breast cancer develops, Tagaya et al [68] constructed bacterial artificial chromosome (BAC)-based PB transposons with a vector size of >200 kb to transfect MaSCs via in vitro EP. They transplanted the transfected MaSCs into cleared fat pads of the inguinal mammary glands (from which the endogenous epithelium had been removed) of immune-deficient mice.…”
Section: Gene Delivery To Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse mammary glands can regenerate completely by the use of mammary stem cells (MaSCs). To examine the mechanism by which breast cancer develops, Tagaya et al [68] constructed bacterial artificial chromosome (BAC)-based PB transposons with a vector size of >200 kb to transfect MaSCs via in vitro EP. They transplanted the transfected MaSCs into cleared fat pads of the inguinal mammary glands (from which the endogenous epithelium had been removed) of immune-deficient mice.…”
Section: Gene Delivery To Mammary Glandmentioning
confidence: 99%
“…They observed correct differentiation of the transplanted cells into both basal and luminal cells, as well as milk production after pregnancy. Tagaya et al [68] also demonstrated that oncogene-induced tumorigenesis is possible when MaSCs transfected with PB transposons, which carry the polyoma-virus middle T antigen gene, are transplanted into mammary glands.…”
Section: Gene Delivery To Mammary Glandmentioning
confidence: 99%
“…However, this engineering approach is not practical for highthroughput and larger-scale gene evaluation. Recently, we reported a transposon-based genetic manipulation system in the mammary gland that can be applied to oncogene screening, lineage tracing, and marker gene screening [1].…”
Section: Genetic Manipulation Of the Mammary Gland And Potential Applmentioning
confidence: 99%
“…However, this engineering approach is not practical for high-throughput and larger-scale gene evaluation. Recently, we reported a transposon-based genetic manipulation system in the mammary gland that can be applied to oncogene screening, lineage tracing, and marker gene screening [1].…”
mentioning
confidence: 99%
“…However, there are intrinsic limitations in introducing long or complex sequences that include multiple promoters or transcription termination sequences owing to their viral packaging mechanism. To address this problem, we recently established another method using the piggyBac transposon system combined with electroporation [1]. The transposon system has almost no restrictions on sequence type or cargo length (> 200 kb BAC) [7], so that the design of complex and long DNA elements, including those for overexpression, knockout, or knockdown experiments, are almost limitless.…”
mentioning
confidence: 99%